2016
DOI: 10.1016/j.ajog.2015.10.919
|View full text |Cite
|
Sign up to set email alerts
|

Length of second stage of labor and preterm birth in a subsequent pregnancy

Abstract: Background During the second stage of labor, it is plausible that the pressure of the fetal head against a completely dilated cervix may lead to changes in the cervical integrity and cervical strength lending it susceptible to premature dilation in a subsequent pregnancy. Therefore, a prolonged second stage of labor has been hypothesized to be a risk factor for cervical insufficiency and spontaneous preterm birth (sPTB). Objective To evaluate the effect that the length of second stage of labor in one pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 8 publications
2
41
0
Order By: Relevance
“…First, prolonged second stage has been evaluated as a possible risk for subsequent SPTB. The first study reported an association, 4 whereas subsequent larger studies 57 failed to find such a link; the current study by Wood et al 1 confirms that, overall, there does not seem to be a consistent association between prolonged second stage (or the length of the second stage in general) in the prior pregnancy and subsequent SPTB. 47 …”
supporting
confidence: 50%
See 4 more Smart Citations
“…First, prolonged second stage has been evaluated as a possible risk for subsequent SPTB. The first study reported an association, 4 whereas subsequent larger studies 57 failed to find such a link; the current study by Wood et al 1 confirms that, overall, there does not seem to be a consistent association between prolonged second stage (or the length of the second stage in general) in the prior pregnancy and subsequent SPTB. 47 …”
supporting
confidence: 50%
“…7 This is an important analysis because it reinforces the fact that it does not seem that prolonged second stage per se increases the future risk of SPTB, but if a CD is done in the second stage, and perhaps even more significantly, with a prolonged second stage, the risk of subsequent SPTB is increased compared with a vaginal delivery.…”
mentioning
confidence: 81%
See 3 more Smart Citations